Measurement of T‐Cell Telomere Length Using Amplified‐Signal FISH Staining and Flow Cytometry. Issue 1 (5th January 2017) - Henning, Andrea L.; Levitt, Danielle E.; Vingren, Jakob L.; McFarlin, Brian K.
Abstract: Exposure to pathogen‐associated molecular patterns (PAMPS), damage‐associated molecular patterns (DAMPS), and physiologically challenging stimuli either positively or negatively affect leukocyte maturity. Cellular maturity has implications for the effectiveness of host response to bacterial or viral infection and/or tissue injury. Thus, the ability to accurately assess cellular maturity and health is important to fully understand immune status and function. The most common technique for measuring cellular maturity is to measure telomere length; however, existing techniques are not optimized for single‐cell measurements using flow cytometry. Specifically, existing methods used to measure telomere length are PCR‐based, making it difficult for a researcher to measure maturity within specific leukocyte subsets (e.g., T cells). In this report, we describe a new approach for the measurement of telomere length within individual T cells using an amplified fluorescence in situ hybridization (FISH) technique (PrimeFlow RNA Assay). The unique aspect of this technique is that it amplifies the fluorescent signal rather than the target up to 3000‐fold, resulting in the detection of as few as 1 copy of the target nucleic acid. While the current technique focuses on human T cells, this method can be broadly applied to a variety of cell types and disease models. © 2017 by John Wiley & Sons, Inc.